Group Threat and Racial Disparities in Police-Caused Killings - Ortiz, Ruben A. (2020)
Blacks, Latinos, and American Indians are killed by police at a disproportionately higher rate than whites and Asians, but whether racial discrimination accounts for these killings remains disputed. I contribute to this debate by assessing whether group threat theory is associated with the overall, and race-specific count of police-caused killings at the metropolitan and county level across the US. Furthermore, I assess whether there is evidence of racial bias in police-caused killings, and if county-level measures of threat are associated with measures of racial bias at the individual level. Using data from the Census Bureau, American Community Survey, The Washington Post, The Guardian, and Uniform Crime Reporting program, my results indicate that the size of the black and Latino population relative to the white population is consistently associated with a higher expected count of police-caused killings of blacks and Latinos at the metropolitan and county level. Moreover, I find that an increase in the size of the black and Latino population relative to the white population across US counties is associated with decreases in the expected count of police-caused killings of all people and white people. I find that regional differences exist in the expected count of police-caused killings across metropolitan areas, and counties. Moreover, my results provide evidence of racial bias in police-caused killings. Among people who were shot and killed by police, Latinos were 1.26 times as likely as whites to have not been attacking people when killed, and blacks were 1.38 times as likely as whites to have been unarmed prior to getting shot by police. deaths. In developing solutions to reduce police-caused killings, researchers should look beyond the proximal causes of death (i.e. the police) to the distal factors operating across metropolitan areas and counties that predict the expected count of police-caused killings of minorities